Upaya Orang Tua Penyandang Disabilitas dalam Membangun Keluarga Sakinah - Indrasyahputra Tambak; Muhammad Ikhsan Ariyogi; Cipto Sembodo; Muthmainnah Muthmainnah; Zainul Arifin; Ahmad Syafii Rahman; Fitriana Firdausi (Universitas Cokroaminoto Yogyakarta, 2025)
This sociological juridical research aims to reveal how parents of people with disabilities in one area of Yogyakarta city strive to realize the goal of a harmonious, loving, and compassionate marriage within their limitations as a family classified as a pre-sakinah family. Following the legal research, social research was conducted by relying on in-depth interviews with two parents with disabilities and village officials related to family life at the research location. Triangulation was carried out by extending the research period. The results showed that these families have made efforts according to their living conditions to achieve this goal. Although material well-being is still a concern, efforts to bestow affection within the family are an important way to achieve the goal of a harmonious marriage.